Animal ethics: an Islamic perspective (Etika dalam melayani binatang: satu perspektif Islam) - Amanullah, Muhammad (Centre of Qur'anic Research, UM, 2012)
Animals are considered to be one of the large groups of the creation of Allah (SWT). According to the Holy Qur’an, they are deemed to be miracles of the Almighty Allah and signs of His existence and Unity. All of them worship Allah in a way that we are unable to see or feel. By and large, all creatures including these animals are created for the benefit of humankind. Some of these animals are consumed as food or meat; some of them are used for riding on their backs or carrying goods; while some others are kept as pets or used for other purposes. Most of them are wild, while some of them are domestic. However, some of them are harmful to mankind. Nowadays, besides the use of plants and bacteria, animal cells are also used for industrial or scientific purposes and for making drugs and chemicals. Human beings often treat these animals with cruelty and fail to treat them ethically. Although during the last century or so a number of organizations for protecting animal rights have been established all over the world, until now many people think that since these animals are created for the benefit of humankind, they do not deserve to be treated nicely. In other words, according to these people, animals should not have any right for themselves. Rather, human beings are allowed to use them as they wish without following any ethics. This view is not acceptable in Islam, which has offered detailed ethical guidelines for treating animals. By analyzing the related verses of the Qur’an and ahadith of the Prophet (p. b. u. h.), this paper intends to discuss importance of animals in Islam and Islamic ethics for treating them. Additionally, based on these ethical guidelines, it strives to prove that these animals have rights, and therefore their rights should be recognized through providing an alternative definition of right (haqq) that includes animals’ rights. The paper may conclude that Islam has offered a balanced and just code of ethics for treating animals and established their rights like the rights of human beings.